Clinically Relevant Solution for the Hypothermic Storage and Transportation of Human Multipotent Mesenchymal Stromal Cells. (20th January 2019) - Petrenko, Yuriy; Chudickova, Milada; Vackova, Irena; Groh, Tomas; Kosnarova, Eliska; Cejkova, Jitka; Turnovcova, Karolina; Petrenko, Alexander; Sykova, Eva; Kubinova, Sarka
Abstract : The wide use of human multipotent mesenchymal stromal cells (MSCs) in clinical trials requires a full-scale safety and identity evaluation of the cellular product and subsequent transportation between research/medical centres. This necessitates the prolonged hypothermic storage of cells prior to application. The development of new, nontoxic, and efficient media, providing high viability and well-preserved therapeutic properties of MSCs during hypothermic storage, is highly relevant for a successful clinical outcome. In this study, a simple and effective trehalose-based solution was developed for the hypothermic storage of human bone marrow MSC suspensions for further clinical applications. Human bone marrow MSCs were stored at 4°C for 24, 48, and 72 hrs in the developed buffered trehalose solution and compared to several research and clinical grade media: Plasma-Lyte® 148, HypoThermosol® FRS, and Ringer's solution. After the storage, the preservation of viability, identity, and therapeutically associated properties of MSCs were assessed. The hypothermic storage of MSCs in the new buffered trehalose solution provided significantly higher MSC recovery rates and ability of cells for attachment and further proliferation, compared to Plasma-Lyte® 148 and Ringer's solution, and was comparable to research-grade HypoThermosol® FRS. There were no differences in the immunophenotype, osteogenic, and adipogenic differentiation and the immunomodulatory properties of MSCs after 72 hrs of cold storage in these solutions. The obtained results together with the confirmed therapeutic properties of trehalose previously described provide sufficient evidence that the developed trehalose medium can be applied as a low-cost and efficient solution for the hypothermic storage of MSC suspensions, with a high potential for translation into clinical practice.